Enforcement actions and their suspension: the concept and legal regulation in Ukraine, Georgia, Kazakhstan, Armenia (Lex Scientia Law Review, 2022)
The purpose of this research paper is to study the concept and legal regulation of enforcement actions and their suspension in Ukraine, Georgia, Kazakhstan, Armenia. The methodology of this article is based on the application of various methods of scientific knowledge, including analytical method, deductive method, synthesis method, hermeneutic method, comparative method, modeling method. The results of scientific research presented in this article contain the author's definitions of "enforcement actions", "suspension of enforcement actions", generalization of legal regulation of enforcement actions and their suspension under the laws of Ukraine, Georgia, Kazakhstan, Armenia. The practical significance of the results presented in the article lies in the possibility of taking them into account both by legal theorists, in particular those working on the subject of enforcement proceedings, and legal practitioners, in particular those involved in the enforcement of various jurisdictional decisions.